Combat time in international female judo: a systematic review and meta-analysis - Mota Barreto, L. B.; Seixas Duarte, T.; Ahmedov, F.; Aedo-Munoz, E. A.; Aidar Martins, F. J.; Sorbazo Soto, D. A.; Miarka, B.; Brito, C. J. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2024)
Background. Rule changes in recent years might have interfered with the time spent in female judo combats. Furthermore, weight divisions may have different temporal combat behaviors and react differently to rule changes.